Naval mutinies of the twentieth century : an international perspective - Bell, Christopher M.; Elleman, Bruce A., 1959- (Cass series--naval policy and history., 2003)
This volume brings together a set of scholarly, readable and up-to-date essays covering the most significant naval mutinies of the 20th century.